Statistical Study on the Motivation of Patients in the Pediatric Dentistry - Lucian Josan; Sorana Maria Bucur; Mariana Păcurar; Elina Teodorescu; Andreea Sălcudean; Cristina Stanca Molnar Varlam; Alina Ormenișan (MDPI AG, 2022)
Our statistical study included 344 participants selected from the patients of the Pedodontics-Orthodontics Discipline of the Tîrgu-Mureş University of Medicine and Pharmacy. The patients' age was between 6 and 18 years, with an average of 13.70 and a standard deviation of 4.62. The study participants were informed and agreed to complete two questionnaires of our conception regarding their health status, oral hygiene, and motivation for pedodontics or orthodontic treatment. The results of the two questionnaires were interpreted according to the gender and age of the patients. Data processing was performed with NCSS/PASS Dawson Edition statistical software, using the CHI2 test, considering a p of less than 0.05 as significant for comparative results. Results showed that girls were more motivated than boys in addressing pedodontic services due to dental, periodontal, and articular problems. Children, aged between 11 and 14 years, were less intrinsically motivated to solve oral health problems due to their low frequency. The intrinsic motivation for a more beautiful dentition was very strong, regardless of age and sex. Girls were more intrinsically motivated for orthodontic treatment than boys. There was a linear increase together in the age of those who wanted to improve their smile and facial appearance. Children between 11 and 14 years had the best self-perception of the appearance of their teeth, mouth, smile, and facial harmony. The strongest extrinsic motivation for orthodontic treatment came from parents or another doctor. The most important reason for orthodontics was dental malpositions, the last one was the improvement of masticatory efficiency. The extrinsic motivation from parents for orthodontics decreases linearly with age, along with the increase in motivation from the person with whom the participants relate emotionally and from the group of friends.